Behind the Stars - Tiffani D. Lawrence (Crossing Borders: A Multidisciplinary Journal of Undergraduate Scholarship, 2017)
From the perspective of the author, “Behind the Stars,” takes a meditative look at ancient Inca astronomy and the culture surrounding both the sky and the idea of darkness. A research-based, creative nonfiction essay in which the author explores the history of an Andean rainforest, the people that used to inhabit it, and the constellations above it. Two types of constellations are discussed from a vantage point near the equator – both light-based constellations and the dark constellations specific to the Inca and Quechua cultures. This essay examines the role of astronomy in the Incas’ everyday life and culture, while viewing the world with a 21st century writer’s awareness. Ancient Inca culture is compared with modern culture in this creative reflection on how people view the world around them, and the ideologies that different cultures embrace. This essay introduces big picture ideas through the frames of history, astronomy, and reflection.
Keywords: Inca Astronomy; Dark Constellations; Maquipucuna; Creative Non-Fiction